Partisipasi Masyarakat Dalam Pembangunan Desa Masbagik Utara Baru Kecamatan Masbagik Kabupaten Lombok Timur Tahun 2020 - M. Ulfatul Akbar Jafar; M. Taufik Rachman; Abdurrahman Abdurrahman; Mardiah Mardiah (JIAP (Jurnal Ilmu Administrasi Publik), 2021)
Community participation is often discussed in various areas, both in urban and rural areas. Community involvement in the development process in the village is a must considering that the village is a milestone of national development, this should also be encouraged in the village of Masbagik Utara Baru, East Lombok district, considering that the village of Masbagik Utara Baru has a there is a lot of potential and a very large village budget supply. This research is descriptive with a qualitative method approach, conducted in the village of Mabagik Utara Baru, the determination of the informants in this study is snowball sampling, and uses triangulation in data collection, namely, interviews, documentation and observation. The results showed that the level of community participation in the village of Masbagik Utara Baru was very good, it was evident from the activeness of the community in every activity carried out by the village, not only activities that were economically empowering, but also socio-religious activities, this was strengthened by the results the research team interviewed the village head and the local BPD head, he said that the Masbagik Utara Baru community is a very open society with developments and people who have a very high spirit of cooperation, almost every activity is always busy and compact, the results of this interview are also reinforced by opinions religious leaders, educators as well as women and youth leaders in the village of Masbagik Utara Baru, where from their opinion it can be concluded that the collegial collective spirit that has traditionally been obtained is an important force in the increasingly positive development process in the village of Masbagik Utara Baru.